INOVASI PROGRAM FORSAM (FORUM SOLUSI SAMPAH MASYARAKAT) SEBAGAI MODEL KOLABORASI MULTIPIHAK DALAM PENGUATAN TATA KELOLA SAMPAH DI KAMPUNG KAWUNEN KELURAHAN TRITIH KOTA SERANG - Herli Noviansyah; Sastra Wijaya; Anita Sukmawati; Silatu Dzikri; Vika Ratih; Siti Nur; Liasa Noviar; Ayu Komalasari; Yayah; Afikoh; Nicki Aldi; Anggi Saputra; Sulaeman; Beye; Gress Nathalia; Usi Anggraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem of waste collection services in Kawunen Village, Teritih Subdistrict, Walantaka District, Serang City, is marked by the halt of collection services due to the previous disposal site no longer being usable. This situation makes it difficult for residents to manage household waste. The KKM activities of Group 19 from Primagraha University aim to establish FORSAM (Community Waste Solutions Forum) as a multi-stakeholder collaborative space to find and determine solutions as well as the mechanisms for waste collection services. The implementation method uses a participatory approach with collaborative governance principles through stages of problem identification, forum formation, solution discussion, third-party coordination, field surveys, agreement, and service implementation. Results show that FORSAM successfully brought together residents, neighborhood groups (RT/RW), community leaders, village government, and third parties to produce an agreement on waste collection services Transportation then resumed so that the community has a more organized mechanism in handling household waste. FORSAM became a form of collaborative innovation as well as a contribution from KKM Group 19 of Universitas Primagraha in supporting the sustainability of waste management services in Kampung Kawunen. Keywords: FORSAM, collaborative governance, waste management, transportation services, KKM.